Biodegradable Plastic Synthesis Based on Kluwih Seeds (Artocarpus camansi) and Chitosan with the Addition of Glycerol - Hidayat, Fadlan; Sunartaty, Rita; Ibrahim; Safiah; Fitriyana, Liya (Postgraduate, University of Mataram, 2023)
The natural resources of agricultural products have the potential to be raw material for making biodegradable plastic, one of which is starch from kluwih seeds (Artocarpus camansi). This study examines the potential of kluwih seed starch as a basic material for making biodegradable plastic. This research method is experimental, the raw material for making biodegradable plastic is the kluwih seed starch originating from Aceh Besar Regency, Aceh Province. Other additives used are chitosan as reinforcement and glycerol as plasticizers. The analysis is carried out, namely mechanical properties, morphology, thermal, functional groups, water absorption and degradation analysis. The results of the analysis of this study show that the kluwih seed starch functions as a basic material for making biodegradable plastic. As chitosan concentration increases, the resulting tensile strength increases with results obtained around 119.17-166.67 kgf/mm2, while the percentage of elongation is lower the results obtained are 6.82-11.15%. The morphological analysis shows the biodegrable plastic produced has a compact and homogeneous structure. The thermal analysis shows a good thermal stability to ranging from 180 to 370 oC. The results of the biodegradable plastic FTIR show wave numbers 1662.64–1049 cm-1. Water absorption analysis is obtained around 7.658-12.068%, a decrease in water absorption is influenced by the addition of chitosan concentration. Biodegradable paltic planted in the soil containing EM4 degraded for 3 days.